2013
DOI: 10.1021/ja402421w
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Properties of Self-Assembled Multinuclear Platinum Metallacycles with Different Conformational Geometries

Abstract: In this work, spectroscopic techniques and quantum chemistry calculations were used to investigate the photophysical properties of various multinuclear platinum complexes with different conformational geometries. This suite of complexes includes a Pt−pyridyl square, a Pt−carboxylate triangle, and a mixed Pt−pyridyl−carboxylate rectangle, as well as two mononuclear Pt model complexes. Studying the individual molecular precursors in the context of larger assemblies is important to provide a complete understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 53 publications
4
46
0
Order By: Relevance
“…[25,26] Herein,t he singlet ( 1 pp*) energy level of H 2 L (270 nm, 1 pp* = 37 040 cm À1 )i se stimated by referring to its wavelength of absorbance edge in the UV spectrum (Figure S2). The triplet ( 3 pp*) energy level of H 2 L( 438 nm: 3 pp* = 22 830 cm À1 )i sd etermined by the low-wavelength emission peak of the phosphorescence of the Gd analog at 77 K ( Figure S8) process is effective in this ligand (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…[25,26] Herein,t he singlet ( 1 pp*) energy level of H 2 L (270 nm, 1 pp* = 37 040 cm À1 )i se stimated by referring to its wavelength of absorbance edge in the UV spectrum (Figure S2). The triplet ( 3 pp*) energy level of H 2 L( 438 nm: 3 pp* = 22 830 cm À1 )i sd etermined by the low-wavelength emission peak of the phosphorescence of the Gd analog at 77 K ( Figure S8) process is effective in this ligand (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, recent reports have demonstrated that platinum-based SCCs can act as effective hosts for guests and have interesting photophysical properties (37)(38)(39)(40)(41)(42). In particular, highly emissive rhomboids based on aniline-containing donors and Pt-based metal acceptors have…”
mentioning
confidence: 99%
“…The excitedstate intramolecular proton transfer (ESIPT) attracts much attention particularly due to its dual emission with large Stokes' shift, which leads to its significant applications in molecular probes [5,[13][14][15][16], laser dyes [17][18][19], luminescent materials [20][21][22], chemosensors [23][24][25][26][27][28][29][30][31] and molecular logic gates [32], etc. Hence, the mechanism investigation of ESIPT is of vital importance to design, synthesize and regulate desired luminescent molecules [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%